Avaliação das atividades antiinflamatória, antiangiogênica e antitumoral de extratos da Arrabidaea chica (Humb. & Bonpl.) B. Verlot - Ana Flavia de Carvalho Ribeiro (2012)
In developing countries traditional medicine based on the use of plant extracts play a majorrole in health care. Arrabidaea chica (HBK) Verlot (Bignoniacea) is a common plant in theAmazon region. Its leaves are widely used in folk medicine for wound healing, treatment ofinflammation, intestinal colic, blood dysfunction, anemia, hemorrhage and leukemia. The antiinflammatoryeffect of its extract was already demonstrated in vitro and in vivo. The aim ofthe present study was to evaluate the cytotoxic activity of extracts of A. chica against humantumor cell lines. Also evaluate the in vivo antitumor activity in mice bearing solid Ehrlichtumor by hematological and biochemical studies, evaluation of the development of the tumorand immunophenotyping of mononuclear inflammatory cells in blood and associated withtumor tissue. The anti-inflammatory activity was evaluated using the murine sponge model.Methanol, ethanol and aqueous extracts were obtained from dried lives of A. chica. Thepresence of the flavonoid kaempferol was verified by high performance liquidchromatography. The ethanol extract (EE) showed cytotoxic activity against Jurkat and HL60leukemic cells, with IC50 values of 27.9 mg / mL and 26.9 mg / mL, respectively. Also,ethanol extract-EE induced DNA fragmentation assessed by flow cytometry assay, suggestingthat the toxicity presented may be related to induction of apoptosis. The ethanol-EE and CA3extracts, administered orally at a dose of 300mg/kg presented anti-inflammatory activityassessed by the murine sponge model. Both extracts inhibited neovascularization andrecruitment of neutrophils to the sponges without altering the macrofage mobilization andvascular endothelial growth factor (VEGF) concentration. There was a reduction in solidtumor volume in mice treated with EE and CA3 (30mg/kg) after 10 days of daily oraladministration (p<0,05) without changes in hematological and biochemical parameters. Theethanol extract-EE increased neutrophils and 1 and globulins, and decreased 2 globulins.The ethanol-EE and CA3 extracts reduced the percentage of T CD4+ cells on blood withoutaltering TCD3+, NK and B lymphocytes. The aqueous fraction CA3 showedimmunomodulatory activity by reducing the number of TCD3+, CD8+ and NK cells in tumortissue, without altering the percentage of B and T CD4+ cells. The extracts did not producetoxic effects in mice in either study. It is concluded that the ethanol extract and aqueousfraction CA3 of A. chica have antitumor effect after oral administration, confirming its use intraditional medicine. The activity of the ethanol extract-EE seems to be related to the potentcytotoxic and pro-apoptotic activities, as well as its anti-inflammatory and antiangiogenicactivities. The antitumor effect presented by the aqueous fraction CA3 is possibly related totheir anti-inflammatory and antiangiogenic activities. These results suggest biotechnologicalpotential of the extracts of A. chica for obtaining new antitumor drugs.